Light intensity regulation of cab gene transcription is signaled by the redox state of the plastoquinone pool. - Escoubas, J M (1995)
The eukaryotic green alga Dunaliella tertiolecta acclimates to decreased growth irradiance by increasing cellular levels of light-harvesting chlorophyll protein complex apoproteins associated with photosystem II (LHCIIs), whereas increased growth irradiance elicits the opposite response. Nuclear run-on transcription assays and measurements of cab mRNA stability established that light intensity-dependent changes in LHCII are controlled at the level of transcription. cab gene transcription in high-intensity light was partially enhanced by reducing plastoquinone with 3-(3,4-dichlorophenyl)-1,1-dimethyl urea (DCMU), whereas it was repressed in low-intensity light by partially inhibiting the oxidation of plastoquinol with 2,5-dibromo-3-methyl-6-isopropyl-p-benzoquinone (DBMIB). Uncouplers of photosynthetic electron transport and inhibition of water splitting had no effect on LHCII levels. These results strongly implicate the redox state of the plastoquinone pool in the chloroplast as a photon-sensing system that is coupled to the light-intensity regulation of nuclear-encoded cab gene transcription. The accumulation of cellular chlorophyll at low-intensity light can be blocked with cytoplasmically directed phosphatase inhibitors, such as okadaic acid, microcystin L-R, and tautomycin. Gel mobility-shift assays revealed that cells grown in high-intensity light contained proteins that bind to the promoter region of a cab gene carrying sequences homologous to higher plant light-responsive elements. On the basis of these experimental results, we propose a model for a light intensity signaling system where cab gene expression is reversibly repressed by a phosphorylated factor coupled to the redox status of plastoquinone through a chloroplast protein kinase.